Kritik Sayid Utsman Bin Yahya terhadap Ideologi Jihad dalam Gerakan Sosial Islam Pada Abad 19 dan 20 - Ahmad Athoillah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2013)
This writing describes the using of jihād ideology in the movement of social fighting in Jawa in the nineteenth and twentieth centuries during the people change within the colonial era. Such social struggle, which is called as holy war, was criticized by Sayid Utsman bin Yahya as an advisor of honorair of the Dutch government. Sayid Utsman then attempted to formulate the meaning of jihād as the religious activities.DOI: 10.15408/ref.v13i5.914